Chemosensory processing in children with attention-deficit/hyperactivity disorder. (May 2016) - Lorenzen, Anna; Scholz-Hehn, Deborah; Wiesner, Christian D.; Wolff, Stephan; Bergmann, Til O.; van Eimeren, Thilo; Lentfer, Luisa; Baving, Lioba; Prehn-Kristensen, Alexander
Abstract: Background: In attention-deficit/hyperactivity disorder (ADHD) not only deficits in dopamine-related cognitive functioning have been found but also a lower dopamine-sensitive olfactory threshold. The aim of the present study was to proof that only olfactory but not trigeminal sensitivity is increased in ADHD. Structural magnetic resonance imaging (MRI) was used to show increased olfactory bulb (OB) volume- a structure which is strongly shaped by olfactory performance through the mechanism of neuroplasticity (e.g. synaptogenesis). To elucidate whether cortical mechanisms are involved in altered olfaction in ADHD, functional MRI (fMRI) was introduced. Methods: A total of 18 boys with ADHD and 17 healthy controls (aged 7–12) were included in the study. Olfactory as well as trigeminal detection thresholds were examined. OB sizes were measured by means of structural MRI and an analysis of effective functional (fMRI) coupling of primary olfactory cortex was conducted. The frontal piriform cortex (fPIR) was chosen as seed region because of its importance in processing both trigeminal and olfactory stimuli as well as having profound influence on inner OB-signaling. Results: Increased olfactory sensitivity as well as an increase in OB volume was found in ADHD. There were no group differences in sensitivity towards a trigeminal stimulus. Compared to healthy controls, the fPIR in ADHD was more positively coupled with structures belonging to the salience network during olfactory and, to a lesser extent, during trigeminal stimulation. Conclusions: Olfactory functioning is superior in subjects with ADHD. The observed increase in OB volume may relate to higher olfactory sensitivity in terms of neuroplasticity. During the processing of chemosensory stimuli, the primary olfactory cortex in ADHD is differently coupled to higher cortical structures which might indicate an altered top-down influence on OB structure and function.